Differences in ecomorphology and trophic niche segregation of two sympatric heptapterids (Teleostei: Siluriformes) (Acta Scientiarum. Biological Sciences, 2020)
Morphological similarity, resource sharing, and differences in habitat use by species are factors that favor their coexistence. The objective of this study was to test possible differences in ecomorphology and diet composition of two Heptapterids (Imparfinis mirini and Cetopsorhamdia iherengi) to identify patterns related to resource use. Samplings were carried out in ten streams in Southern Brazil and 123 individuals were caught. A total of 21 ecomorphological indices were calculated for each individual and the volumetric and occurrence methods were used to quantify stomach contents. Both species presented significant differences in some ecomorphological traits, mainly related to foraging behavior. Even though both species were considered insectivorous, the consumed feeding resources differed between them. Cetopsorhamdia iheringi diet was dominated by Simuliidae and terrestrial Coleoptera larvae, while Imparfinis mirini, presented a diet dominated mainly by Trichoptera larvae, Ephemeroptera nymph, and Annelida. Although ecomorphological patterns cannot be used as an absolute factor to explain diet variations, they provide relevant information about how species share resources. These mechanisms allow us to obtain important subsidies for the conservation and management of freshwater ecosystems since they provide an effective understanding on the interactions that occur between the species.